2022
DOI: 10.31219/osf.io/zx7nh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrepancies between Objectively Assessed and Self-Reported Daily Social Media Time in the Age of Platform Swinging

Abstract: Building on Junco’s (2013) study examining the accuracy of self-reported computer-specific time on Facebook, the current study investigates the accuracy of self-reported time on multiple social media (SM) platforms across multiple electronic devices and evaluates whether reporting accuracy is systematically associated with participant sex, individual SM platform in question, or total number of SM platforms used. Participants were 320 college students who downloaded software on their computers, tablets, and sma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It was found that information value, social interaction value and self-presentation value had significantly positive impacts on consumers’ brand community-swinging, which further fosters brand loyalty [ 42 ]. Bolye et al examined the accuracy of self-reported computer-specific time on multiple social media platforms and evaluated the influencing factors of reported accuracy based on platform swinging context [ 43 ]. Zhang et al investigated how Chinese journalists navigate multiple social media platforms and employ data-driven source as complements to traditional source in practices during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that information value, social interaction value and self-presentation value had significantly positive impacts on consumers’ brand community-swinging, which further fosters brand loyalty [ 42 ]. Bolye et al examined the accuracy of self-reported computer-specific time on multiple social media platforms and evaluated the influencing factors of reported accuracy based on platform swinging context [ 43 ]. Zhang et al investigated how Chinese journalists navigate multiple social media platforms and employ data-driven source as complements to traditional source in practices during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…First, in most empirical studies we exclusively relied on self-report measures for assessing technology usage. However, self-report measures do not correlate strongly with non-obtrusive log data of smartphones and SNS (Boyle et al, 2022;Ernala et al, 2020;P. H. Lee et al, 2021;Marengo et al, 2021;Parry et al, 2021;Rozgonjuk, Pruunsild, et al, 2020).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%